Pengaruh Inflasi dan Tingkat Suku Bunga Terhadap Penanaman Modal Asing di Provinsi Sumatera Utara Tahun 2013-2020 - Hasibuan, Silvia Annur; Manik, Monika Flora; Sianturi, Rejosu Vanhot; Harahap, Evi Suriyani (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study was conducted to examine in depth the effect of inflation and interest rates on Foreign Direct Investment (FDI) in North Sumatra Province during the period 2013 to 2020. This study uses a quantitative approach with secondary data in the form of time series data obtained from the Central Statistics Agency and other related agencies. The analysis method used is multiple linear regression. The results of the study show that the inflation variable has a positive and significant effect on FDI in North Sumatra Province, which indicates that stable and controlled inflation is perceived as a reflection of healthy economic activity and promising market potential for foreign investors. On the other hand, the interest rate variable has a negative and significant effect on FDI, which means that an increase in interest rates can reduce the interest of foreign investors due to the high cost of capital and investment risk. Simultaneously, both variables have a significant effect on FDI, with a coefficient of determination of 78.1%. This shows that inflation and interest rates together are able to explain most of the variation in the level of FDI entering the North Sumatra region. This study concludes that macroeconomic stability, especially related to inflation control and interest rate policies, plays a fundamental role in attracting foreign investment. Therefore, synergy of government policies is needed in creating a conducive business environment, providing legal certainty, simplifying regulations, and maintaining macroeconomic indicators in a stable condition.